Outside-in engineering of cadherin endocytosis using a conformation strengthening antibody - Bin Xie; Shipeng Xu; Sanjeevi Sivasankar (Nature Communications)
Abstract P-cadherin, a crucial cell-cell adhesion protein which is overexpressed in numerous malignant cancers, is a popular target for drug delivery antibodies. However, molecular guidelines for engineering antibodies that can be internalized upon binding to P-cadherin are unknown. Here, we use a combination of biophysical, biochemical, and cell biological methods to demonstrate that trapping the P-cadherin extracellular region in an X-dimer adhesive conformation triggers cadherin endocytosis via an outside-in signaling mechanism. We show that the anti-cancer drug delivery monoclonal antibody CQY684, traps P-cadherin in an X-dimer conformation and strengthens this adhesive structure. Formation of stable X-dimers results in the phosphorylation of p120-catenin, a suppressor of cadherin endocytosis. This triggers the dissociation of p120-catenin from the X-dimer cytoplasmic region, which increases P-cadherin turnover and targets the cadherin-antibody complex to the lysosome. Our results establish an outside-in signaling mechanism that provides fundamental insights into how cells regulate adhesion and that can be exploited by anti-cadherin antibodies for intracellular drug delivery.